Community Matters : Challenges to Civic Engagement in the 21st Century. - Gehring, Verna V. (Institute for Philosophy and Public Policy studies., 2005)
In Community Matters: Challenges to Civic Engagement in the 21st Century, six distinguished scholars address three perennial challenges of civic life: the making of a citizen, how citizens are to agree (and disagree), and how to define the rights and responsibilities of citizenship. These essays will encourage students, academics, and interested citizens outside the academy to go farther and dig deeper into these vital issues.